Dampak bullying terhadap perkembangan psikologi anak - Mustofa, Muhammad Royhan (Maliki Interdisciplinary Journal, 2024)
This research examines the role of the environment in child development. Various environmental factors such as economic conditions, quality of education, social interactions, and physical conditions are analyzed to understand their impact on children’s cognitive, emotional, and social development. This study combined qualitative and quantitative methods to collect data from a sample of children with diverse backgrounds. The research results show that a supportive and positive environment significantly contributes to children’s optimal development, while a less supportive environment can hinder their growth and development. These findings emphasize the importance of public policies and interventions aimed at creating an environment conducive to child development.